Heterogeneous Perceptions of Social-Ecological Change Among Small-Scale Fishermen in the Central Gulf of California: Implications for Adaptive Response - Frawley, Timothy H.; Crowder, Larry B.; Broad, Kenneth (Frontiers in Marine Science, 2019)
As changes in climate, governance, and organization reshape the dynamics of small-scale fisheries around the globe, the persistence of many local livelihoods appears contingent upon the ability of resource users to respond and adapt. Though significant scholarship has considered the limiting roles of resources and infrastructure, recent research has highlighted the importance of local learning and knowledge. Rather than being driven by forces exogenous to local communities, it is increasingly recognized that adaptation may be limited by perceptions and processes within them. Here we explore knowledge production and adaptive response within a small-scale fishery in the central Gulf of California following system perturbation. Using mixed methods from the natural and social sciences, we 1) identify local drivers of socio-ecological change, 2) document knowledge concerning their causes and consequences across a diverse group of small-scale fishermen and 3) identify patterns of intracultural agreement and disagreement associated with divergent adaptive response. Results indicate that perceptions of socio-ecological change were heterogeneous and that gear ownership and target species diversification were critical factors in determining the cultural models through which fishermen understood and responded to changes in the resource system. Unlike other user groups, owner-operator fishermen pursuing generalist livelihood strategies held consensus beliefs regarding changes to system structure and function and demonstrated increased ability to modify fishing tactics with the best practices for sustainable use. Our findings highlight how local knowledge can be used to assess the proximate impacts of external drivers of change and provide insight into the cultural models influencing in situ decision-making and adaptive response within modern fishery systems.